Assessing Opioid Shopping Behaviour: A Large Cohort Study from a Medication Dispensing Database in the US - Cepeda, M. Soledad; Fife, Daniel; Chow, Wing; Mastrogiovanni, Gregory; Henderson, Scott C. (Drug safety, 2012)
Background: Risks of abuse, misuse and diversion of opioids are of concern. Obtaining opioid prescriptions from multiple prescribers, known as opioid shopping, is a way in which opioids may be abused and diverted. Previous studies relied on counting the number of prescribers or number of pharmacies a subject goes to in a year to define shopping behaviour, but did not distinguish successive prescribers from concomitant prescribers. Objective: The aim of the study was to assess the frequency of opioid overlapping prescriptions from different prescribers, compare it with diuretics and benzodiazepines, and provide a definition of shopping behaviour that differentiates opioids from diuretics, avoiding the inappropriate flagging of individuals with legitimate use of opioids. Study Design: Population-based cohort study using the IMS LRx database. This database covers 65% of all retail prescriptions in the US and includes mail service and specialty pharmacy provider prescriptions independent of the method of payment. Setting: Ambulatory. Patients: Subjects with at least one dispensing for any type of opioid in 2008. Similar cohorts were created for subjects exposed to benzodiazepines or diuretics. Analyses were performed separately for naı¨ve subjects and those with prior use. Outcome: Frequency of overlapping prescriptions defined as at least 1 day of overlapping dispensing of prescriptions written by two or more different prescribers at any time during an 18-month period. Results: A total of 25 161 024 subjects exposed to opioids were included, of whom 13.1% exhibited at least one episode of overlapping prescriptions during 18 months of follow-up. Almost 10% of subjects exposed to benzodiazepines and 13.8% of subjects exposed to diuretics exhibited a similar behaviour. Having overlapping prescriptions dispensed by three or more pharmacies differentiates opioids from the other medication classes. Using that criterion, the overall risk of shopping behaviour was 0.18% in subjects exposed to opioids, 0.10% in subjects exposed to benzodiazepines and 0.03% in subjects exposed to diuretics. For opioids, subjects aged between 25 and 64 years exhibited shopping behaviour more commonly (0.25%) than subjects 65 years or older (0.07%), and subjects with a history of prior opioid use exhibited such behaviour more commonly (0.7%) than opioid-naı¨ve subjects (0.07%). Conclusion: Overlapping of prescriptions is not unique to opioids and therefore a criterion that incorporates number of pharmacies is needed to define shopping behaviour. Having two or more overlapping prescriptions written by different prescribers and filled at three or more pharmacies differentiates opioids from diuretics and likely constitutes shopping behaviour.